Proyecto de libro fotográfico e interactivo de la parroquia de Loja el Valle de Vilcabamba - Vivanco Aguirre, Alejandro (2016)
Vilcabamba Valley has been known worldwide as "The Island of Longevity" by having people that easily exceed the 100 years old. It is located at 40 Km to the east of Loja city in southern Ecuador. It is a valley at 1,700 meters above sea level, watered by rivers Chamba and Uchima. It has innumerable and majestic landscapes with an unprecedented history among its habitants, architecture and nature. The Spanish Luis Fernando de la Vega founded it on September 1, 1576. Unfortunately, despite being considered International Tourist Center (Municipality of Loja, 2012), the visual and audiovisual content that is possessed of this village is very low, with poor quality and superficial in its majority. Affecting this to its own people that today live mostly from tourism. Vilcabamba has been for several of its features a magical valley, but its most effective publicity has simply been the verbal advertising of its visitors, being wasted in such a way the audiovisual technological advancement. For these reasons, this work of end of career aims to develop a visual and audio content of this historic valley, which will be able to emonstrate and present all the special it is and how spectacular it really is. Revealing the touristic and study attraction, through a different and more complete audiovisual initiative as an interactive photo book with transmedia narrative, which takes the user to appreciate the valley in a more complete way, with extra audiovisual material and the implementation of virtual reality. Similarly, the new technique booming video and photography at 360º degrees, where the Internet user can interact with the video by scrolling through it to choose what to see, will be one of the ways to be used to show the landscapes of the valley in a deeply way.